Analisa Kapasitas Force Draft Fan Dengan Bahan Bakar Batubara Kualitas Rendah - Arief Suardi Nur Chairat; Rahmadino Yuda (JURNAL POWERPLANT, 2016)
Coal power plant is designed based on a particular coal quality. Changes in coal quality will affect the quality of combustion and changes in combustion air. This study will describe the analysis of changes in coal quality on the ability of the force draft fan covers theoretical air, the percentage of air, capacity and force draft fan itself, and to analyze whether the capacity of force draft fan that existed at the time the design is adequate to the quality of coal that apply now .Berdasarkan calculation of theoretical air force draft fan air is 306 300 kg / s with the design power of 811 909 kW. Calculation of actual data shows the average air flow in the period from March to May was 307 610 kg of air / s. The capacity is still inadequate because of changes in the quality of the coal used is not too large.